2022
DOI: 10.1515/multi-2021-0013
|View full text |Cite
|
Sign up to set email alerts
|

Sharing communicative responsibility: training US students in cooperative strategies for communicating across linguistic difference

Abstract: The internationalization of Anglophone universities could allow English-dominant students to benefit from experience with English speakers from a wide variety of backgrounds, but US students have often complained of difficulty communicating with such instructors, especially International Teaching Assistants (ITAs). Research has largely focused on helping ITAs assimilate linguistically and culturally, although many applied linguists suggest that ITAs’ students would also benefit from training in skills for comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Also, assigning the second and third ranks to speaking and writing reflects the importance of these two skills in the workplace setting. This finding supports the role of oral and written communication in the workplace, and this has been confirmed by several previous studies (Al-mahrooqi and Denman, 2017;Subtirelu, et al, 2022;Kashyap, 2021) Most importantly, the results are related to the respondent"s awareness of the content, activities, materials, and quizzes that must be considered when developing the course. Regarding the content selection for workplace English, the findings revealed the participants" preferences for the mixed option: general and specific topics.…”
Section: Discussion Of Findingssupporting
confidence: 88%
“…Also, assigning the second and third ranks to speaking and writing reflects the importance of these two skills in the workplace setting. This finding supports the role of oral and written communication in the workplace, and this has been confirmed by several previous studies (Al-mahrooqi and Denman, 2017;Subtirelu, et al, 2022;Kashyap, 2021) Most importantly, the results are related to the respondent"s awareness of the content, activities, materials, and quizzes that must be considered when developing the course. Regarding the content selection for workplace English, the findings revealed the participants" preferences for the mixed option: general and specific topics.…”
Section: Discussion Of Findingssupporting
confidence: 88%
“…Thus, biased belief might influence the representation of speech in memory, but not on-line language processing. This hypothesis seems to be encouraging as reduced comprehension might be due to listeners' unwillingness, which might be alleviated by some intervention (Subtirelu et al, 2022).…”
Section: Discussionmentioning
confidence: 91%
“…That errors arising from linguistic difference can therefore occur because learners are not fully aware of the grammar of the target language, they can therefore unknowingly assimilate some grammatical patterns. Subtirelu et al (2022) found that learners in his course had orientations on the linguistic difference between languages, without which, learning foreign language would probably be impossible. The difference between Kiswahili and French is generally considered by Manyasa, J.…”
Section: Literature Reviewmentioning
confidence: 99%